Cost-sharing in medical care can increase adult mortality: Evidence from Colombia - Giancarlo Buitrago; Javier Amaya-Nieto; Grant Miller; Macos Vera-Hernandez (Institute for Fiscal Studies (IFS), 2023)
There is substantial evidence that cost-sharing in medical care constrains total health spending. However, there is relatively little (and unclear) evidence on its health effects, particularly in low- and middle-income countries. This paper re-evaluates the link between outpatient cost-sharing and health, studying Colombia's entire formal sector workforce observed monthly between 2011 and 2018 with individual-level health care utilization records linked to payroll data and vital statistics. Because Colombia's national health system imposes discrete breaks in outpatient cost-sharing requirements across the earnings distribution, we estimate a dynamic regression discontinuity model, finding that greater outpatient cost-sharing initially reduces use of outpatient care (including consultations and drugs), resulting in fewer diagnoses of common chronic diseases - and over time, increases the prevalence and severity of chronic diseases as well as use of inpatient care. Ultimately, greater outpatient cost-sharing measurably increases mortality, raising 8-year mortality by 4 deaths per 10,000 individuals. To the best of our knowledge, this study is the first to show a relationship between cost-sharing and adult mortality risk in a low- or middle-income country, a relationship important to incorporate into social welfare analyses of cost-sharing policies.
Keywords: 330